Caminhos do lembrar: a construção e os usos políticos da memória no morro do Borel - Amoroso, Mauro (2012)
The aim of this work is to develop a reflection on the process of construction and the political uses of memory in the Borel. To achieve this goal, we will analyze the book 'The struggles of the people of Borel,' written by Manoel Gomes, a local resident and former communist militant, and the Condutores de Memória project, carried out by residents of the favelas of Borel and Casa Branca in partnership with the Agenda Social Rio, we intend to consider the characteristics of the articulation of different actors in the development of storage media slum dwellers from the case of Borel and how different historical contexts can interfere the instrumentalization of memory as a political claim.